Perspectives of evolution of legal solutions concerning entrusting by local self-government units the public tasks to perform with other entities against the background of Polish law - Wioleta Baranowska-Zając (Juridical Tribune, 2019)
On the local self-government units - municipalities, counties and voivodships - exercising public administration in Poland on the principle of decentralization of public authority, there are numerous public tasks to perform, including in particular the own tasks serving the collective needs of members of local self-government community. These tasks could be carried out by local self-government units using their own entities - organizational units, budgetary establishments, as well as municipal companies created - but could also be entrusted to perform with other, separate entities, especially non-public entities. The forms of entrusting by local self-government units the tasks with entities outside self-government structure are regulated by Polish Act of 1996 on municipal economy. The provisions of this Act were subject to several amendments in the analyzed scope. With entrusting by local self-government units the public tasks to separate entities, especially non-public entities, there are connected numerous problems that have not been solved so far. They concern the subjective scope of entities to which it is possible to entrust public tasks by self-government units, the basis and nature of the entrustment, the scope of entrustment, the legal status of the entity entrusted with tasks, obtained as a result of entrusting public tasks, the principles on which the entrustment is based, the effects of entrusting, the responsibility for performing the entrusted tasks. Taking the above into account, the scientific purpose of the research is an identification and determination of specific problems related to entrusting the performance of public tasks by local self-government units with separate entities, especially private entities, against the background of Polish law and determination of the perspectives of evolution of legal solutions concerning such entrusting.